Antibiotic-associated diana, intelligent Clostridium difficiary - Moskaliuk, V. D.; Rudan, I. V.; Balaniuk, I. V.; Myronyk, O. V.; Andrushchak, M. O. (Zaporozhye Medical Journal, 2018)
Objective: To study antibiotic-associated diarrhea due to Clostridium difficile. Materials and methods: a retrospective and prospective analysis of literature and studies on C. difficile antibiotic-associated diarrhea was conducted. Results Despite the concerted efforts to improve the prevention and treatment of C. difficile infection, this infection remains common and serious both in hospitals and among the population. In recent years, germ cell transplantation has emerged as a safe and effective strategy for treating relapsing infections. With further improvement, the microbial transplantation of feces is likely to become the standard of care for periodic infections. Despite the fact that antibiotic therapy and decontamination in health facilities remain important for infection control, effective probiotics and vaccination are likely to become important tools for preventing infection C. difficile in the future. By this time, C. difficile infection continues to be a common and very painful consequence of the use of antibiotics. Pathogenic C. difficile strains form two protein exotoxins, toxin A and toxin B, which cause damage to the intestinal mucosa and inflammation. The infection can be asymptomatic, cause mild diarrhea or cause severe pseudomembranous colitis. The first step is to stop the use of an antibiotic that causes diarrhea. If diarrhea and colitis are serious or persistent, then the drugs of choice are metronidazole and vancomycin. Clostridium difficile is an anaerobic gram-positive, spore-forming, toxin-producing bacilli that is transmitted to humans through the fecal-oral transmission mechanism. In the United States, C. difficile is the most frequently reported nosocomial pathogen in 2011, with 453,000 cases of C. difficile infection and 29,000 deaths associated with C. Difficile infection. Conclusions. To date, the incidence of C. difficle-infections has increased, due to the wide and often uncontrolled use of antibiotics. It should be noted that antibiotic-associated diarrheas due to C. difficile occupy one of the first places in the structure of morbidity and mortality among infectious diarrheas, representing a serious and antimicrobial problem of therapy in the conditions of the in-patient and among the population. CDI has become an increasingly common infection and has shown an increase in severity over the past few years.